Ensino e aprendizagem de língua inglesa a partir da internet: reflexões acerca do canal English in Brazil - Sangalli, Rosane (2019)
The teaching of languages, from virtual learning contexts, is a very discussed topic in contemporary times by many researchers and teachers who investigate ways to reconcile technology and teaching when learning a foreign language. In general, the use of technologies in language teaching has reached its space in the educational sector, because of the advancement of information and communication technologies, the knowledge is increasingly accessible in the digital world. In view of this, it becomes relevant to research the use of technology for education, analysing the different kinds of learning the virtual community offers us. This study is anchored in the sociocultural theory of the Russian psychologist Lev Semyonovich Vygotsky, Parâmetros Curriculares Nacionais and specialists from the language teaching area, dealing with important concepts which guide the teaching and learning process. As a methodological approach, the study seeks to research the YouTube educative channel, called English in Brazil, by the teacher Carina Fragozo, based on a quantitative and qualitative research, through an online questionnaire applied with her followers, in order to, theoretically, reflect how the process of teaching and learning, in a motivating way, through the internet occurs. Therefore, it was possible, through this study, to verify that the Internet helps in the process of knowledge construction, causing the learners to reach their goals in English language in an interactive way.